Radiologic and Blood Markers Predicting Long-Term Neurologic Outcome Following Decompressive Craniectomy for Malignant Ischemic Stroke: A Preliminary Single-Center Study - Paracino, Riccardo; De Domenico, Pierfrancesco; Rienzo, Alessandro DI; Dobran, Mauro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Malignant ischemic stroke (MIS) is defined by progressive cerebral edema leading to increased intracranial pressure (ICP), compression of neural structures, and, eventually, death. Decompressive craniectomy (DC) has been advocated as a lifesaving procedure in the management of patients with MIS. This study aims to identify pre- and postoperative predictive variables of neurologic outcomes in patients undergoing DC for MIS.Methods We conducted a retrospective study of patients undergoing DC in a single center from April 2016 to April 2020. Preoperative workup included baseline clinical status, laboratory data, and brain computed tomography (CT). The primary outcome was the 6-month modified Rankin score (mRS). The secondary outcome was the 30-day mortality.Results During data capture, a total of 58 patients fulfilled the criteria for MIS, of which 22 underwent DC for medically refractory increased ICP and were included in the present analysis. The overall median age was 58.5 years. An immediate (24 hour) postoperative extended Glasgow Outcome Scale (GOSE) score ≥5 was associated with a good 6-month mRS (1–3; p = 0.004). Similarly, low postoperative neutrophils (p = 0.002), low lymphocytes (p = 0.004), decreased neutrophil-to-lymphocyte ratio (NLR; p = 0.02), and decreased platelet-to-lymphocytes ratio (PLR; p = 0.03) were associated with good neurologic outcomes. Preoperative variables independently associated with worsened 6-month mRS were the following: increased age (odds ratio [OR]: 1.10; 95% confidence interval [CI]: 1.01–1.20; p = 0.02), increased National Institutes of Health Stroke Scale (NIHSS) score (OR: 7.8; 95% CI: 2.5–12.5; p = 0.035), Glasgow Coma Scale (GCS) score less than 8 at the time of neurosurgical referral (OR: 21.63; 95% CI: 1.42–328; p = 0.02), and increased partial thromboplastin time (PTT) before surgery (OR: 2.11; 95% CI: 1.11–4; p = 0.02). Decreased postoperative lymphocytes confirmed a protective role against worsened functional outcomes (OR: 0.01; 95% CI: 0.01–0.4; p = 0.02). Decreased postoperative lymphocyte count was associated with a protective role against increased mRS (OR: 0.01; 95% CI: 0.01–0.4; p = 0.02). The occurrence of hydrocephalus at the postoperative CT scan was associated with 30-day mortality (p = 0.005), while the persistence of postoperative compression of the ambient and crural cistern showed a trend towards higher mortality (p = 0.07).Conclusions This study reports that patients undergoing DC for MIS showing decreased postoperative blood inflammatory markers achieved better 6-month neurologic outcomes than patients with increased inflammatory markers. Similarly, poor NIHSS score, poor GCS score, increased age, and larger PTT values at the time of surgery were independent predictors of poor outcomes. Moreover, the persistence of postoperative compression of basal cisterns and the occurrence of hydrocephalus are associated with 30-day mortality.
Keywords: decompressive craniectomy; malignant ischemic stroke; prognostic factors